Midodrine for the early liberation from vasopressor support in the ICU (LIBERATE): a feasibility study - Sebastian J. Kilcommons; Fadi Hammal; Dawn L. Opgenorth; Kirsten M. Fiest; Constantine J. Karvellas; Vincent I. Lau; Erika MacIntyre; Janek Senaratne; Jocelyn Slemko; Wendy Sligl; Fernando Zampieri; D.’Arcy Duquette; et al. (Pilot and Feasibility Studies)
Abstract Background Intravenous (IV) vasopressors are the mainstay of physiological support for hemodynamically unstable patients. However, the role of oral vasopressors remains unclear. The objective of our study was to evaluate the feasibility of evaluating midodrine for critically ill patients with IV vasopressor-dependent shock. Methods We conducted a single-center, concealed-allocation, parallel-group, blinded feasibility randomized controlled trial (RCT) evaluating the effect of oral midodrine versus placebo on IV vasopressor-dependent shock in the intensive care unit (ICU). The study was performed in a medical-surgical ICU at the University of Alberta Hospital from April 2021 to July 2022. We included patients aged 18 years or older admitted to the ICU with ongoing vasopressor support with decreasing vasopressor dose(s). Patients were randomly assigned 1:1 to midodrine or a placebo for the duration of their IV vasopressor therapy. The primary outcome was study feasibility and secondary outcomes included patient-centered outcomes. Feasibility was assessed through rate of recruitment, adherence to study protocol, and patient safety. Results Twenty patients were enrolled in the study and underwent randomization (n = 11 midodrine, n = 9 control). Recruitment was recorded at 1.2 participants per month, protocol adherence was 90%, and allocation remained concealed. No adverse events were reported in either group. Sepsis was the most common cause of shock in both groups. The midodrine group had a shorter length of ICU stay of 9.6 (SD 8.7) vs 10.4 (SD 14.5) days. Hospital mortality was lower for the midodrine group (n = 2, 18.2% vs n = 4, 37.5%). Vasopressor re-initiation after 24 h was more frequent in the midodrine group (n = 4, 36.4% vs n = 2, 25%). There were no readmissions to the ICU following discharge in either group. Conclusions The evaluation of midodrine for patients in the ICU is feasible and safe. This trial will inform future large-scale RCTs regarding the utility of midodrine in critically ill patients with IV vasopressor-dependent shock. Trial registration This pilot RCT was registered at clinicaltrials.gov (NCT04489589). Registered July 27, 2020. https://clinicaltrials.gov/study/NCT04489589